2010
DOI: 10.1007/s11258-010-9819-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Campanula glomerata threatened by competition from expanding grasses? Results from a 5-year pot-experiment

Abstract: The disappearance of low-intensity types of agricultural land use such as mowing and grazing is a global phenomenon which leads to changes in species composition and interactions in plant communities. In central Germany, formerly species-rich, semi-natural dry grasslands have been converted into species-poor communities dominated by Festuca rupicola or Poa angustifolia. As a consequence, several forbs have become endangered, and biodiversity has decreased. In a 5-year competition experiment (replacement design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Similar results were found in competition experiments between the grass species F. rupicola and the rare and low-growing Alyssum montanum (Partzsch et al, 2011), and with the endangered and declining dry grassland species Campanula glomerata (Bachmann et al, 2005;Partzsch and Bachmann, 2010). These results support the assertion of Aarssen and Keogh (2002), and of Freckleton et al (2009) who argue that most studies of plant competition have the risk being incorrect in that they tend to only focus on the measurement of growth responses to competition and ignore fecundity.…”
Section: Performance Of Dianthus Carthusianorumsupporting
confidence: 78%
“…Similar results were found in competition experiments between the grass species F. rupicola and the rare and low-growing Alyssum montanum (Partzsch et al, 2011), and with the endangered and declining dry grassland species Campanula glomerata (Bachmann et al, 2005;Partzsch and Bachmann, 2010). These results support the assertion of Aarssen and Keogh (2002), and of Freckleton et al (2009) who argue that most studies of plant competition have the risk being incorrect in that they tend to only focus on the measurement of growth responses to competition and ignore fecundity.…”
Section: Performance Of Dianthus Carthusianorumsupporting
confidence: 78%
“…Working with species mixtures of insect-pollinated plants, Baude et al (2011) found that the presence of a strong plant competitor led to a decrease in the total amount of sugar allocated to nectar in the less competitive one, probably through soil resource depletion. Likewise, the presence of a neighbouring wind-pollinated competitor reduced the flower production of an insect-pollinated one, C. glomerata (Partzsch & Bachmann, 2011), and Flacher et al (2015) found that competition induced by wind-pollinated plants led to a decrease in floral display size and flower size, but also total flower production and total sugar allocated to nectar in two annual insect-pollinated species. In this last experiment, the stronger the competitor, the stronger the effect on attractiveness traits.…”
Section: Introductionmentioning
confidence: 99%
“…competition for abiotic resources between plants), could thus play a key role in plant-pollinator networks. However, to our knowledge, while the effect of plant competition for abiotic resources on floral traits has been studied (Baude et al, 2011;Partzsch & Bachmann, 2011;Flacher et al, 2015), the indirect role of such competition on pollinator behaviour, through modifications of floral traits involved in plant attractiveness, has never been investigated. In addition, wind-pollinated species are almost never taken into account in plant-pollinator studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller, less competitive species usually benefit from mowing because they are harmed less by cutting and they are often able to recover quickly because of a release from competition pressure. Removal of biomass, which usually follows mowing, also prevents accumulation of dead biomass (Ruprecht et al 2010;Partzsch and Bachmann 2011).…”
Section: Species Richness á Western Carpathians á Grassland Managementmentioning
confidence: 99%